Let's analyze the steps provided in solving the equation:
-
The original equation is:
\( 3x - 9x + 1 = 2(-3x + 1) - 1 \) -
Simplifying the left side:
\( 3x - 9x + 1 = -6x + 1 \)
This is what we get after simplifying. -
Simplifying the right side:
\( 2(-3x + 1) - 1 = -6x + 2 - 1 = -6x + 1 \) -
Now we can equate both sides:
\( -6x + 1 = -6x + 1 \)
At this point, we see that both sides of the equation are identical.
This implies that the equation is always true regardless of the value of \( x \). Therefore, there are infinitely many solutions to the equation, as every value of \( x \) satisfies it.
Correct Statement:
There are infinitely many solutions to the equation.